2023
DOI: 10.1101/2023.12.03.569825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saturation resistance profiling of EGFR variants against tyrosine kinase inhibitors using prime editing

Younggwang Kim,
Hyeong-Cheol Oh,
Seungho Lee
et al.

Abstract: Variants of uncertain significance (VUS) hamper the clinical application of genetic information. For example, in treating lung cancer with tyrosine kinase inhibitors (TKIs), many epidermal growth factor receptor (EGFR) variants remain classified as VUS with respect to TKI sensitivity1,2. Such incomplete resistance profiles hinder clinicians from selecting optimal therapeutic agents3,4. A high-throughput approach that can evaluate the functional effects of single nucleotide variants (SNVs) could reduce the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Another effort examined dropout phenotypes from nonsense mutations targeted to one essential gene ( RPL15 ) with the PE2 approach and found that variant effects were categorized as depleting more often when endogenous site sequencing was used to determine phenotypes than without (80% of nonsense variants called as detrimental while only 32% were called using epegRNA abundances; 25 total variants targeted). 30 When evaluating the same gene in our StopPR screen, we observed negative growth phenotypes (Z < −2) for 77.8% (7/9) of targeted nonsense variants with at least one stop epegRNA without endogenous target site sequencing. Our results therefore compare favorably to contemporary platforms and demonstrate the ability to measure high-specificity and reliable phenotypes from epegRNA abundance alone.…”
Section: Discussionmentioning
confidence: 88%
“…Another effort examined dropout phenotypes from nonsense mutations targeted to one essential gene ( RPL15 ) with the PE2 approach and found that variant effects were categorized as depleting more often when endogenous site sequencing was used to determine phenotypes than without (80% of nonsense variants called as detrimental while only 32% were called using epegRNA abundances; 25 total variants targeted). 30 When evaluating the same gene in our StopPR screen, we observed negative growth phenotypes (Z < −2) for 77.8% (7/9) of targeted nonsense variants with at least one stop epegRNA without endogenous target site sequencing. Our results therefore compare favorably to contemporary platforms and demonstrate the ability to measure high-specificity and reliable phenotypes from epegRNA abundance alone.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, we used SynDesign to develop a saturation resistance profiling library of the EGFR gene against various the chemotherapy drugs, afatinib and osimertinib. A SGE library was designed and evaluated to profile over 2476 SNVs in the EGFR gene that included 95% (1726/1817) of the possible protein variants in the tyrosine kinase domain (exons 18–21) which represents an important functional hotspot for cancer-related mutations ( 4 , 14 ). SynDesign was able to compile a list of all feasible pegRNAs targeting every position in the EGFR gene to systematically evaluate this important oncogene.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, introducing a synonymous mutation adjacent to the intended edit on the target DNA have been shown to improve on-target prime editing efficiency by diffusing the local cellular MMR activity ( 3 ). Additionally, the synonymous mutation can serve as an indicator of properly edited targets following deep sequencing ( 4 ). Taken together, the application of prime editing for saturation genome editing (SGE) can be a powerful tool in conducting systematic functional screening of variants for target genes of interest, especially for investigating variants of uncertain significance (VUS) that represent a major portion of the single nucleotide variants (SNVs) on the ClinVar and COSMIC databases, 95% and 99%, respectively (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%